Tax Administration : Designing a Business Continuity Plan for an Epidemic - Brondolo, John.; Aslett, Joshua; Komso, Andja (Washington, D.C. : International Monetary Fund, 2020)
This technical note and manual (TNM) addresses the following questions: What is a business continuity plan (BCP) and what are its main components? What are a BCP's key design considerations for an epidemic? What are the organizational and management arrangements for a BCP? How does a BCP maintain a tax agency's critical functions during an epidemic? and How does a tax agency keep its BCP current and ready for deployment?
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Continuity Plan; Crisis Management; Tax Administration